UPAYA PENINGKATAN KESEHATAN KERJA MELALUI PENDEKATAN POSISI ERGONOMI PADA KARYAWAN PT. INTIDRAGON SURYATAMA KABUPATEN MOJOKERTO - Mujiadi; Henry Sudiyanto; Siti Rachmah (JURNAL PENGABDIAN MASYARAKAT KESEHATAN (ABDIMAKES), 2023)
Musculoskeletal Disorders (MSDs) are problems that are often faced by workers. Workers whose work position is not ergonomic are at high risk of experiencing work injuries or accidents. This service is carried out as an effort to improve occupational health through the application of the right attitude at work, namely working ergonomically. Efforts that can be given are to provide rest periods sitting in the seats provided during working time, this condition aims to reduce fatigue in workers with monotonous work for a long time. The method used in community service is in the form of a questionnaire about complaints of musculoskeletal pain namelyNordic body maps (N.B.M.). The target audience in this activity are employees of PT. Intidragon Suryatama as many as 35 people. The results in this activity were as many as 6 people (17%) employees did not complain of pain in the muscles. As many as 24 people (69%) employees complained of feeling a little sore, a little sore in the muscles but their work was not disturbed. As many as 5 people (14%) employees complained of pain in the muscles so that their work was disrupted but after there was time to rest, the complaints disappeared. It is hoped that the K3 sector within the company will hold training and educational program activities regarding work processes so that workers can understand and be able to adapt to their work environment and the equipment used, these activities are an effort to reduce the incidence of work accidents through adjustments to the work environment.